The Effect of HIV Education Program on Changing the Attitude of Secondary School Students Towards HIV/AIDS Sufferers Khartoum State (2014) - Omer, Duria Abdelraheim Mohammed Ahmed; Ahmed Omer, Nagla Abdelrahim Mohammed (مجلة الجزيرة للعلوم الصحية; مجلد 13 عدد 2 (2017), 2017)
HIV/AIDS seriously affects adolescents throughout the world. One-third of all currently infected individuals are youth ages 15 to 24, and half of all new infections occur in same age youth. This is an Interventional Quasi study, aimed to assess the effect of health education program of Human Immune -Deficiency virus on changing attitude towards HIV and AIDS among secondary school students in Khartoum state. Five hundred students were enrolled by using multi stage random sampling, the study was done in three phases: phase one used questionnaire of 32 questions. Phase two was implementing the Sudanese National Aids Program (SNAP'S) which is a health education program in secondary schools alongside the curriculum for students in the selected secondary schools for 8 months. Phase three was Re- Evaluation by the same questionnaire used in phase one. The study revealed that few students were willing to care of a family member or friend who suffers with AIDS (25.6%) in the pre-test however the percentage increased to  (79.2%)  after intervention, (42.6%)  thought that HIV positive people should not be allowed to mix with people at mosque or church , the percentage decreased to (39.2%) after the intervention. 63.8% of students said that a teacher who is HIV positive should not be allowed to continue teaching in their school, while only (86.2%) of the students changed their mind after intervention. Also prior to intervention (27.6%) of the students accepted sharing same class with HIV infected student while (50.0%) agreed after the intervention. The study concluded that education intervention program was effective and statistically significant in the Improvement of students' attitude towards HIV/AIDS positive (P value= 0.001) . معظم اصابات فيروس  مرض نقص المناعة المكتسب تحدث وسط الشباب من عمر 14-24 سنه هذه دراسه تدخليه تهدف الى تقييم أثرتدريس كتيب البرنامج القومى السودانى للايدز للتثقيف الصحى على سلوك  عينة من طلاب المدارس الثانوية بولاية الخرطوم تجاه  المصابين بالفيروس أو مرضى الأيدز و التى اشترك فيها (500) طالب تم اختيارهم عشوائيا بطريقة التعدد المرحلى . نفذت الدراسة على ثلاثة مراحل : المرحلة الأولى تم فيها جمع المعلومات بواسطة استبيان مكون  من(32) سؤال , ثم مرحلة التدخل عن طريق تدريس الذى وضع بواسطه البرنامج السودانى القومى للايدز  لمدة سته اشهر, ثم المرحلة الثالثة و التى جمعت فيها البيانات بنفس الاستبيان الأول . توصلت الدراسة الى النتائج الآتية: 25.6% من الطلاب كانوا موافقين على رعاية مريض ايدز ينتمى الى الأسرة قبل التدخل بينما ارتفعت النسبة الى 79.2% بعد التدخل . 42.2% رأوا أن المصاب بالفيروس لا يجب ان يختلط بالناس فى المسجد و قد نقصت النسبة بعد التدخل الى 39.2%. 63.8% من الطلاب قبلوا بتلقى الدراسة من معلم مصاب بالفيروس قبل التدخل و قد ارتفعت النسبة الى 86.2% بعد التدخل. كما لم يمانع 27.6% منهم على وجود زميل لهم بالفصل مصاب بالفيروس قبل التدخل  و ارتفعت النسبه الى 50.0% بعد التدخل . خلصت الدراسة الى أن منهج التثقيف الصحى للطلاب ذو أثر بالغ احصائيا  فى تحسين إتجاهات طلاب المدارس الثانوية  تجاه المصابين بفيروس نقص المناعة المكتسب أو تجاه مرضى الايدز .